1987
DOI: 10.1002/bjs.1800740113
|View full text |Cite
|
Sign up to set email alerts
|

Intraduct enterokinase is lethal in rats with experimental bile-salt pancreatitis

Abstract: Controlled intraduct infusion and peri-acinar dispersal of 100 microliter buffer containing sodium glycodeoxycholate (GDOC) at concentrations of 8.5, 17 and 34 mmol/l in rats caused a progressively severe acute pancreatitis from which none of the animals died over the experimental period. Infusion of affinity-purified active human enterokinase in buffer did not cause pancreatitis, presumably because of the inability of the macromolecule to gain access to its specific intracellular substrate trypsinogens. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…The first experimental biliary acute pancreatitis model was established by Bernard in 1856 via retrograde injection of bile and olive oil into the pancreas of a canine[ 95 ]. Since then, various bile salts such as sodium chenodeoxycholate[ 96 ], sodium taurocholate, sodium glycodeoxycholic acid[ 97 ], sodium-taurodeoxycholate and taurolithocholic acid 3-sulphate have been reported to induce acute pancreatitis in different animal models. Among these bile salts, the taurine-conjugated bile salt sodium taurocholate was the most widely used and best characterized chemical for the induction of acute pancreatitis[ 98 ].…”
Section: Experimental Tools To Dissect the Mechanism That Promotes Pamentioning
confidence: 99%
“…The first experimental biliary acute pancreatitis model was established by Bernard in 1856 via retrograde injection of bile and olive oil into the pancreas of a canine[ 95 ]. Since then, various bile salts such as sodium chenodeoxycholate[ 96 ], sodium taurocholate, sodium glycodeoxycholic acid[ 97 ], sodium-taurodeoxycholate and taurolithocholic acid 3-sulphate have been reported to induce acute pancreatitis in different animal models. Among these bile salts, the taurine-conjugated bile salt sodium taurocholate was the most widely used and best characterized chemical for the induction of acute pancreatitis[ 98 ].…”
Section: Experimental Tools To Dissect the Mechanism That Promotes Pamentioning
confidence: 99%
“…An early study demonstrated that ductal infusion of 100 µl of the glycine‐conjugated bile salt, Na‐GDC, at concentrations of 8.5 m m , 17 m m and 34 m m , caused progressive, severe but non‐lethal AP in rats 33 . Na‐GDC infusions of 17 m m and 34 m m caused oedematous and necrotizing pancreatitis, respectively 34–36 .…”
Section: Induction Of Ap By Bile Saltsmentioning
confidence: 99%
“…Na‐GDC infusions of 17 m m and 34 m m caused oedematous and necrotizing pancreatitis, respectively 34–36 . When 200 ng enterokinase was administrated with 34 m m Na‐GDC infusate, necrotic pancreatitis with systemic disturbance and rapid lethality was produced 33 …”
Section: Induction Of Ap By Bile Saltsmentioning
confidence: 99%
“…Importantly, TLCS which has been extensively characterized in vitro, is generally preferred over NaTC for inducing PDI-AP, especially after the identification of the G protein-coupled bile acid receptor1 (Gpbar1) present on the apical pole of PACs (Perides et al, 2010). Mice lacking this receptor (Gpbar1 −/− ) were completely protected against AP induced by TLCS in vivo as well as treatment with 500 µM TLCS of PACs isolated from these mice did not result in pathophysiological Ca 2+ responses, intrapancreatic trypsinogen activation, and cell death that are normally seen in wild type Sun et al, 2006Sun et al, , 2007 NaGDC 8.5, 17, or 34 mM 100 µl Rats NaGDC at concentrations of 8.5-34 mM caused progressive severe but non-lethal acute pancreatitis in rats; 17 and 34 mM NaGDC infusion produced oedematous and necrotizing pancreatitis respectively; when 200 ng EK was infused with 34 mM NaGDC, necrotising pancreatitis with systemic disturbance, and rapid lethality was produced Terry et al, 1987;Rattner et al, 1990;Rosen and Tuchler, 1992 5 or 10 mM 100-150 µl Rats Low concentration of NaGDC with i.v., caerulein 5 µg/kg/h injection for 6 h caused features of moderate onset, homogeneous moderate pancreatic injury that lasts over at least 24 h Schmidt et al, 1992a,b NaTDC 2, 5, or 6% 200 µl Rats 2% NaTDC infusion caused pancreatic oedema, leukocytosis, and gradually increase of acinar cell necrosis over time until 24 h; with higher concentration at 5 or 6%, pancreatic necrosis progressed more rapidly Jin et al, 2008Jin et al, , 2011Lopez-Font et al, 2010 NaTC 3, 4.5, or 5% 1 ml/kg Rats Significantly increased serum amylase, lipase, and pro-inflammatory cytokine levels; pancreatic oedema, vacuolisation, inflammation, hemorrhage, acinar cell and fat necrosis; lung, liver, gastric, kidney, and brain injuries; at concentrations of 3.0, 4.5, or 5.0% induced 72 h mortality rates of 24, 71, and 100%, respectively. Paszt et al, 2004;Yang et al, 2004;Leveau et al, 2005;Dang et al, 2007;Zhang et al, 2007;Chen et al, 2008;de Campos et al, 2008;Qian et al, 2010;Xia et al, 2010;Jung et al, 2011 2, 4, or 5% 2 ml/kg Mice 2% NaTC caused oedema, leukocyte infiltration, necrosis, hemorrhage, and fat necrosis of the pancreas without lung injury and lethality; higher dose of NaTC increased pulmonary BAL fluid albumin and myeloperoxidase activity, and mortality: 10 and 60% mortality rates at 24 h for 4 an...…”
Section: Bile Acidsmentioning
confidence: 99%